Bifurcation nation: American penal policy in late mass incarceration - Seeds, Christopher (Punishment & society, 2017)
The question has been posed whether current developments in American penal policy toward reducing prison populations and sentences for low level, nonviolent offenses might reflect the end of the mass incarceration era. Yet articulation of precisely what defines the present in American penal policy remains unclear. This paper identifies three distinctive features: a national-level program of comprehensive criminal justice reevaluation and reform in response to the excesses of recent policy; the distinguishing of groups for distinct treatments as a central principle and product of the reform program; and the fusion of previously distinct political and administrative logics that undergird the reform process. Rather than a full turn away from mass incarceration or an ambivalent mix of old and new, contemporary penal policy is better characterized as a bifurcation, responding uniquely, with new answers and new omissions, to the dilemmas and constraints of “late mass incarceration.”